SOME APPLICATIONS OF THE CHAIN METHOD IN SOLVING A LINEAR DIFFERENCE EQUATION OF FINITE ORDER - Круглов, Віктор (SWorldJournal, 2025)
A scheme of the chain method for solving a finite linear differential equation given in this paper, and a formula for this equation`s general solution of is given. As a result, the formula for the general solution of a differential equation with constant